Efficacy and Safety of Microsurgical Subinguinal Varicocelectomy with and without Testicular Delivery for Varicocele Patients: A Systematic Review and Meta-Analysis - Liao, Bo; Liu, Junbo; Chen, Shuangquan; Zhang, Qiang; Xie, Chaofan; Jiang, Guo; Cui, Shu; Wu, Tao (Urology Journal, 2019)
Purpose: This study reviewed the efficacy and safety of the microsurgical subinguinal varicocelectomy (MSV) with and without testicular delivery (TD) for varicocele patients. Materials and Methods: A systematic literature search was conducted in EMBASE, PubMed, MEDLINE, Cochrane databases, China National Knowledge Infrastructure (CNKI), Chinese Biomedical Literature Database (CBM), and Google Scholar databases to identify relevant studies that reported MSV with and without TD for varicocele patients published in English or Chinese up to October 2018. The Newcastle-Ottawa Scale (NOS) and the Jadad scores were used to evaluate the methodological quality of all the included studies. We also used the Cochrane Collaboration’s tool for assessing risk of bias for each study. The Review Manager Software version 5.3 was used to conduct data analysis. Results: Four RCTs and three retrospective studies consisting of 993 patients were included. Meta-analysis results indicated that both of the two treatments were effective and safe. MSV with TD had a lower recurrence rate (OR = 0.20, 95% CI: 0.06 - 0.65, P = .007, I2 = 0%) and postoperative serum testosterone level (MD = -39.07, 95% CI: -51.95 - -26.18, P = .00001, I2 = 0%) compared with MSV without TD but was associated with higher postoperative complications rate (OR=7.35, 95% CI: 2.92-18.53, P < .0001, I2 = 0%). We found no significant differences in operation time (MD = 12.46, 95% CI:0.11-24.81,P= .05, I2 = 87%), sperm concentration (MD = 3.73, 95% CI: -2.88 - 10.35, P = .27, I2 = 81%), sperm motility (MD = 10.96, 95% CI: -11.93 - 33.86, P = .35, I2 = 99%), and pregnancy rate(OR = 0.65, 95% CI: 0.37- 1.16, P = .15, I2 = 0%). Conclusion: This meta-analysis compared efficacy and safety of MSV with and without TD for varicocele patients. MSV with TD was associated with a higher postoperative complication rate but lower recurrence rate and postoperative serum testosterone level than MSV without TD. In terms of preoperative serum testosterone level, operation time, sperm concentration, sperm motility, and pregnancy rate, we found no significant differences.